Highly efficient RNA-guided base editing in rabbit - Zhiquan Liu (Nature Portfolio, 2018)
Base editors can make targeted changes without inducing a double-stranded break. Here, the authors apply the BE3 and ABE7.10 systems to rabbit to create highly efficient targeted base substitutions and various mutation types, and show reduced frequency of undesired by-products with the updated BE4-Gam system.